2004
DOI: 10.1590/s0103-90162004000300008
|View full text |Cite
|
Sign up to set email alerts
|

Digestive and functional properties of a partially hydrolyzed cassava solid waste with high insoluble fiber concentration

Abstract: Starch factories generate large amounts of cassava solid waste. A small amount is utilized for animal feed but most of it is discharged with deleterious effects to the envirounment. A edible food with a high content of insoluble dietary fiber (60.9%), named "partially hidrolyzed cassava waste" (PHCW), was prepared from industrial cassava solid waste by an enzymatic process. PHCW or wheat bran (WB) were fed to model rats and both promoted digestive function effects, but PHCW produced the greatest effect. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…The flour prepared in this study showed proportions of total dietary fiber at least 19.3 g 100 g -1 greater than commercial wheat brans analyzed by Raupp et al (2000Raupp et al ( , 2004a, which are considered a major source of conventional fiber for human consumption.…”
Section: Resultsmentioning
confidence: 78%
“…The flour prepared in this study showed proportions of total dietary fiber at least 19.3 g 100 g -1 greater than commercial wheat brans analyzed by Raupp et al (2000Raupp et al ( , 2004a, which are considered a major source of conventional fiber for human consumption.…”
Section: Resultsmentioning
confidence: 78%
“…As hortaliças frescas, como a beterraba, possuem baixas proporções de fibra alimentar devido ao alto teor de água, em comparação com as secas. Considerando a importância das fibras alimentares para a saúde humana (SCHWEIZER; EDWARDS, 1992), alguns produtos farináceos como as farinhas integrais e farelos de cereais, os produtos farináceos de mandioca, de maçã e de palmito concentrados em fibras (ALESSI et al, 2003;RAUPP et al, 2004aRAUPP et al, e b, 2000, bem como a farinha de beterraba produzida na pesquisa atual, por ser fonte expressiva de fibra alimentar pode ser usada para aumentar a proporção de fibras em alimentos formulados. A fibra alimentar é a fração constituinte do alimento que resiste à hidrólise pelos sucos digestivos até o intestino delgado humano; mas, ao alcançar o intestino grosso, tem a maior parte de sua fração solúvel extensamente degradada pela biota natural microbiana, enquanto a fração insolúvel permanece quase que totalmente intacta.…”
Section: Resultsunclassified
“…These fibers contribute to the digestive function by stimulating the gastrointestinal peristalsis, making it easier for the fecal excretion of harmful substances from the body, and are thus considered to have protective functions (RAUPP et al, , 2004aEDWARDS, 1992). In this way fiber Acta Scientiarum.…”
Section: Introductionmentioning
confidence: 99%
“…New farinaceous products and dehydrated fruits with high dietary fiber content have been developed in recent research to also become part of the healthy diet of many Brazilians. Many studies used byproducts or wastes generated by agricultural industries, including from processing cassava starch (RAUPP et al, 2002(RAUPP et al, , 2004a, corn (ALESSI et al, 2003), apple , and, more recently, from the heart-of-peach palm agribusiness. In other studies were developed dehydrated fruit and vegetables that do not meet standards for marketing as fresh products (ARAÚJO FILHO et al, 2011;PORFÍRIO-DA-SILVA et al, 2011;RAUPP et al, 2007RAUPP et al, , 2008bRAUPP et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation